Perioperative neurocognitive disorders: a comprehensive review of terminology, clinical implications, and future research directions - Ren, Xuli; Huiqiao, Lian; Wu, Yuntu; Zhang, Te; Chen, Peng; Li, Longyun; Zhao, Guoqing; Wang, Fang (Frontiers in Neurology, 2025)
Perioperative neurocognitive disorders (PNDs) encompass a spectrum of cognitive impairments that may affect patients before, during, or after surgical procedures, with significant implications for patient outcomes, and healthcare expenditures. This comprehensive review examines the evolution of PND terminology, clinical manifestations, diagnostic criteria, incidence rates, risk factors, underlying mechanisms, preventive measures, management strategies, and future research directions. The authors emphasize the importance of early diagnosis and intervention to enhance postoperative recovery and underscore the necessity of a multidisciplinary approach to patient care.